The Legal Position of Crown Witnesses as Evidence in Corruption Trials: A Narrative Literature Review - Putri, Dwi Noviani (Open Access Indonesia Journal of Social Sciences, 2022)
The use of crown witness evidence can only be seen in criminal cases in the form of participation, and separation of those criminal cases has been carried out since the preliminary examination process at the investigative level. Some parties argue that the use of crown witnesses is permissible because it aims to achieve a sense of public justice. However, some are of the opinion that the use of crown witnesses is not permissible because it is contrary to the basic rights and sense of justice of the accused. This is because the crown witness has the status of a defendant and has the right to remain silent or even the right to give answers that are denied or lie. This review aims to describe the use of crown witnesses and the power of crown witness statements in corruption trials in Indonesia.